АРХАИКАЛЫҚ МИФЛЕРДИҢ ӘЙЙЕМГИ ДЕРЕКЛЕРИ ҲӘМ ХАЛЫҚ ДӘСТАНЛАРЫНДА ҚӘЛИПЛЕСИЎ ЖОЛЛАРЫ - Есебаев, М. (SCIENCE and SOCIETY, 2020)
The article deals with the problems of interrelation of poetic structure and mythical motives in national epos of Karakalpak people on the basis of comparative analysis are studied their typological and literary features of transferring of methological motives into the plot of the epos.